Static Stretching, Dynamic Stretching dan Self Mulligan Mobilization untuk Meningkatkan ROM Sendi Leher - Faisal Isra Maulana; Indasah Indasah; Novita Anna (FORIKES, 2024)
Self mulligan mobilization is a special technique for the spine to increase range of motion and reduce pain by correcting positional errors that occur in the spinal joints. Static stretching is a technique that is useful for increasing flexibility, preventing injury, improving performance, reducing the risk of injury in runners and accelerating muscle recovery. Dynamic stretching is used before doing sports activities because it is effective in increasing muscle strength before exercising. This study aimed to analyze the effectiveness of the combination of static stretching and self mulligan mobilization; and the combination of dynamic stretching and self mulligan mobilization to increase the range of motion of the neck joints. The research design used in this study was pretest and post test with control group. This study involved 27 administrative employees, who were then divided into 3 groups, namely: 1) a combination of static stretching and self mulligan mobilization, 2) a combination of dynamic stretching and self mulligan mobilization, 3) a control group. In each group, range of motion measurements were carried out in the form of a cervical spine functional test using a goniometer, both in the phases before and after the intervention. Furthermore, a paired samples t-test and Anova test were carried out. The results of the analysis showed that in the six types of range of motion, there was a significant change after the intervention (p value = 0.000), except for the control group. In the six types of range of motion, the p value for the comparison test between the three groups was 0.000, so it was concluded that there was a difference between the three groups. Based on the post hoc test, the first and second treatment groups produced better range of motion. It was concluded that the combination of static stretching and self mulligan mobilization and the combination of dynamic stretching and self mulligan mobilization were effective in increasing the range of motion of the neck joint.Keywords: neck joint; range of motion; static stretching; dynamic stretching; selfmulligan mobilization ABSTRAK Self mulligan mobilization adalah teknik khusus bagi tulang belakang untuk meningkatkan range of motion dan mengurangi nyeri dengan cara mengoreksi kesalahan posisi yang terjadi pada sendi tulang belakang. Static stretching merupakan teknik yang bermanfaat untuk meningkatkan fleksibilitas, mencegah cedera, meningkatkan performa, menurunkan resiko cedera pada pelari dan mempercepat pemulihan otot. Dynamic stretching digunkan sebelum melakukan aktivitas olahraga karna efektif dalam meningkatkan kekuatan otot saat sebelum berolahraga. Penelitian ini bertujuan untuk menganalisis efektivitas kombinasi static stretching dan self mulligan mobilization; serta kombinasi dynamic stretching dan self mulligan mobilization untuk meningkatkan range of motion sendi leher. Desain penelitian yang digunakan dalam studi ini adalah pretest and post test with control group. Penelitian ini melibatkan 27 karyawan administrasi, yang selanjutnya dibagi menjadi 3 kelompok yaitu: 1) kombinasi static stretching dan self mulligan mobilization, 2) kombinasi dynamic stretching dan self mulligan mobilization, 3) kelompok kontrol. Pada setiap setiap kelompok dilakukan pengukuran range of motion berupa cervical spine functional test dengan menggunakan goniometer, baik pada fase sebelum dan sesudah intervensi. Selanjutnya dilakukan paired samples t-test dan Anova. Hasil analisis menunjukkan bahwa pada keenam macam range of motion, terjadi perubahan signifikan setelah dilakukan intervensi (nilai p = 0,000), kecuali kelompok kontrol. Pada keenam macam range of motion, nilai p untuk uji perbandingan antara ketiga kelompok adalah 0,000, sehingga disimpulkan bahwa ada perbedaan di antara ketiga kelompok. Berdasarkan uji post hoc, kelompok perlakuan pertama dan kedua menghasil range of motion yang lebih baik. Disimpulkan bahwa kombinasi static stretching dan self mulligan mobilization dan kombinasi dynamic stretching dan self mulligan mobilization efektif untuk meningkatkan range of motion sendi leher.Kata kunci: sendi leher; range of motion; static strethcing; dynamic stretching; selfmulligan mobilization